Adaptability evaluation of improved Tomato (Lycopersicon esculentum Mill.) varieties for yield and other quantitative traits in Arba Minch, Southern Ethiopia (International Journal of Agricultural Research, Innovation and Technology, 2022)
Tomato is one of the important vegetables grown all over the world for its nutritious and economic value. Varietal improvement for high yielding, pest resistance and tolerance, drought tolerance and processing quality traits are vital thereby to enhance production and productivity of the crop. Due to lack of improved varieties in the study area, local productivity of tomato is challenged and its production is very limited. Hence, identification of improved tomato varieties that are adaptable, high yielding and disease resistant is crucial before dissemination to boost its productivity in the study area. Therefore, this experiment was conducted at Arba Minch to evaluate ten improved tomato varieties for yield and yield components under irrigation condition using randomized complete block design replicated three times. ANOVA result indicated that there is a significant variation among tested varieties in all studied parameters. The mean total yield and number of fruits plant-1 of tomato varieties varied from 4991.1 to 11,215 kg ha-1 and 13.33 to 36.53 fruits plant-1, respectively. ‘Melkashola’ scored the highest marketable yield (9,438 kg ha-1) and total yield (11,216 kg ha-1) being followed by ‘Bishola’ (8,756 kg ha-1) and ‘Melkasalsa’ (8,367 kg ha-1). On the other hand, ‘Melkasalsa’ and ‘Miya’ with moderately high yield might also be regarded as other potential varieties. Therefore, the first three varieties are recommended for cultivation in the study area and similar agro-ecology.Int. J. Agril. Res. Innov. Tech. 12(1): 79-83, June 2022